ANALISIS MINAT BELAJAR SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN STEM PADA MATERI VEKTOR DI KELAS X MIPA 3 SMAN 2 JEMBER - Irma Septiani; Albertus Djoko Lesmono; Arif Harimukti (Universitas Jember, 2020)
This research to describe the learning interests of students of class X MIPA 3 of SMAN 2 Jember on vector material using the Problem Based Learning model with STEM approach. The method used in this study is a survey using a questionnaire. Indicators of learning interest questionnaire include feelings of pleasure, attention, interest, and student participation. The questionnaire has 20 statements that represent indicators of student interest in learning. The questionnaire was distributed to students of SMAN 2 Jember in MIPA 3 class X, with a total of 36 students. The average percentage results obtained for each indicator are feeling happy 72.3% in the